The Black Arts Enterprise and the Production of African American Poetry - Rambsy, Howard (Book collections on Project MUSE., 2011)
The outpouring of creative expression known as the Black Arts Movement of the 1960s and 1970s spawned a burgeoning number of black-owned cultural outlets, including publishing houses, performance spaces, and galleries. Central to the movement were its poets, who in concert with editors, visual artists, critics, and fellow writers published a wide range of black verse and advanced new theories and critical approaches for understanding African American literary art. The Black Arts Enterprise and the Production of African American Poetry offers a close examination of the literary culture in which BAM's poets (including Amiri Baraka, Nikki Giovanni, Sonia Sanchez, Larry Neal, Haki Madhubuti, Carolyn Rodgers, and others) operated and of the small presses and literary anthologies that first published the movement's authors.